High-pressure zinc oxide phase as visible-light-active photocatalyst with narrow band gap. Issue 38 (19th September 2017) - Razavi-Khosroshahi, Hadi; Edalati, Kaveh; Wu, Ji; Nakashima, Yuki; Arita, Makoto; Ikoma, Yoshifumi; Sadakiyo, Masaaki; Inagaki, Yuji; Staykov, Aleksandar; Yamauchi, Miho; Horita, Zenji; Fuji, Masayoshi
Abstract : High-pressure rocksalt ZnO with a band gap of 1.8 eV, which can absorb visible light. Abstract : Wide band gap of pure ZnO with wurtzite crystal structure (3.1–3.4 eV) limits its photocatalytic activity to the ultraviolet (UV) region of solar spectrum. High-pressure rocksalt polymorph of ZnO can theoretically show narrow band gap; however, the rocksalt phase is unstable at ambient pressure. Herein, rocksalt phase with large fractions of oxygen vacancies is successfully stabilized at ambient conditions by inducing plastic strain in pure ZnO under 6 GPa using the High-Pressure Torsion (HPT) method. Formation of rocksalt phase reduces the band gap of ZnO to 1.8 eV, which is in good agreement with the first-principles calculations, and significantly improves the photocatalytic activity under visible light.